On spaces of special elliptic n-gons - Franco, Felipe de Aguilar (2018)
We study relations between special elliptic isometries in the complex hyperbolic plane. A special elliptic isometry can be seen as a rotation around a fixed axis (a complex geodesic). Such an isometry is determined by specifying a nonisotropic point p (the polar point to the fixed axis) and a unitary complex number a, the angle of the isometry. Any relation between special elliptic isometries with rational angles gives rise to a representation H(k1;:::;kn) → PU(2;1), where H(k1;:::;kn) : = ⟨ r1; : : : ; rn ∣ rn : : : r1> = 1; rkii = 1 ⟩ and PU(2;1) stands for the group of orientation-preserving isometries of the complex hyperbolic plane. We denote by Rpα the special elliptic isometry determined by the nonisotropic point p and by the unitary complex number α. Relations of the form Rpnαn : : :Rp1α1 = 1 in PU(2;1), called special elliptic n-gons, can be modified by short relations known as bendings: given a product RqβRpα, there exists a one-parameter subgroup B : R → SU(2;1) such that B(s) is in the centralizer of Rqβ Rpα and RB(s)qβRB(s)pα = RqβRB(s)pα for every s ∈ R. Then, for each i = 1,...,n-1, we can change Rpi+1αi+1Rpiαi by RB(s)pi+1αi+1RB(s)piαi obtaining a new n-gon. We prove that the generic part of the space of pentagons with fixed angles and signs of points is connected by means of bendings. Furthermore, we describe certain length 4 relations, called f -bendings, and prove that the space of pentagons with fixed product of angles is connected by means of bendings and f -bendings.